Social Media Marketing and Sustainability of Small and Medium Enterprises (SMEs) During COVID-19 Pandemic: Case Study of Gucheez, Central Java, Indonesia - Mohammad Fuad Fauzul Mu'tamar; Millatul Ulya; Burhan Burhan; Fajar Kurniawan (Agriekonomika, 2023)
The Covid-19 pandemic harms the countries' economies, particularly in small and medium enterprises (SMEs). To stay in business, they must be able to adapt to digital technology. Traditional product marketing must transform into digital marketing, including social media marketing. This research aims to examine social media marketing and its impact on the sustainability of SMEs. This study employs a qualitative descriptive research design. This study reveals that SMEs must be able to use social media marketing to maintain their sustainability. In challenging situations, SMEs become more creative and innovative to adapt to the digital technology era. The company remains sustainable, and the company's financial condition has improved as a result of the implementation of social media marketing.